The Go-Kart for pre-primary - "Hunt, Roderick" (Oxford University press, 1986)
The Go-Kart" by Roderick Hunt is a story from the Oxford Reading Tree series featuring familiar characters as they embark on an exciting adventure with a go-kart. In this tale, the children work together to build and race their own go-kart, facing challenges and learning valuable lessons about cooperation and problem-solving along the way. The story emphasizes friendship, creativity, and the joy of play, making it engaging for young readers. With its lively illustrations and relatable themes, it encourages kids to use their imagination and enjoy outdoor activities.
Keywords: Textbook